2013
DOI: 10.1111/rego.12017
|View full text |Cite
|
Sign up to set email alerts
|

To enforce or not to enforce? Judicialization, venue shopping, and global regulatory harmonization

Abstract: The regulation of intellectual property rights takes place in a range of international venues. This proliferation of international venues greatly enhances the potential for venue shopping. We argue that different levels of domestic regulation and differing degrees of judicialization account for actors' preferences over institutional venues. We take into consideration two scenarios. Conceiving of judicialization as the delegation of adjudication to an independent third party and the enforcement through multilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…A second set of considerations concerns the WTO. A number of scholars have identified the WTO as the most important international actor when it comes to “regulatory governance” – understood as the legal, technocratic, and juridical control shaping the behavior of market actors in domestic and other settings (Shaffer ; De Bièvre & Thomann ). The key arguments center on market‐liberalization consequences of participation in the WTO: restrictions on tariffs, limits to anti‐competitive industry practices, the favoring of export‐oriented industries, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…A second set of considerations concerns the WTO. A number of scholars have identified the WTO as the most important international actor when it comes to “regulatory governance” – understood as the legal, technocratic, and juridical control shaping the behavior of market actors in domestic and other settings (Shaffer ; De Bièvre & Thomann ). The key arguments center on market‐liberalization consequences of participation in the WTO: restrictions on tariffs, limits to anti‐competitive industry practices, the favoring of export‐oriented industries, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the causal dynamics going from GVCs to international institutions, one contribution focuses on how GVCs affect the performance of a global, and highly legalized institutions such as the World Trade Organization (WTO). The WTO stands out as a prime example of strong legalization and delegation of authority in international politics (De Bièvre et al., ). The functioning of a governance system which regulates over €23 trillion in trade in goods and services on a yearly basis, ultimately depends on its judicial arm's ability to prevent opportunistic behavior by its members, and on its ability to restore compliance when these are found to violate WTO rules.…”
Section: Institutions and Gvcsmentioning
confidence: 99%
“…One of our interviewees indicated that ‘ the main driver of the tobacco market now is regulation, by far’ and that in this context a multilateral challenge by TTCs to national legislation that risked spillover to other markets, is a logical step (Author interview, May 2016). As such, our analysis provides new insights into MNE lobbying in international trade disputes over domestic regulations and complement the emerging scholarship on the political economy of international regulation and “regulatory capture” (De Bièvre et al 2014; Lawton et al 2009; Roemer-Mahler 2013; Woll and Artigas, 2007; Young 2012; Young 2016). The findings presented here also confirm earlier research (Eckhardt and de Bievre 2015), which indicates that in order to undertake transnational CPA, companies need to be facing a real and existential threat, that they need to be highly globalized, concentrated, well- organized and endowed.…”
Section: Discussionmentioning
confidence: 61%
“…Such challenges have become increasingly common in the global economy and, despite growing scholarly attention (De Bièvre et al 2014; Lawton et al 2009; Roemer-Mahler 2013; Young 2012; Young 2016), we know surprisingly little about the effect of this shift in lobbying by economic actors. In this endeavor, we not only aim to provide insights into firm lobbying on trade issues, but also on transnational lobbying more generally.…”
Section: Introductionmentioning
confidence: 99%